THE INFLUENCE OF VISUAL MERCHANDISING, STORE ATMOSPHERE, AND CREDIT CARD USAGE ON IMPULSIVE BUYING BEHAVIOR AT KKV BALI - Sang Ayu Putu Putri Santika Dewi; Ni Made Rastini (Adisam Publisher, 2024)
Consumer shopping activities can be conducted with planning or without planning (impulsive buying). Impulsive buying is a phenomenon that occurs quite frequently, and companies aim to leverage this phenomenon to boost their sales. To face business competition, KKV Bali requires strategies to encourage impulsive buying among its customers. This study aims to determine the influence of visual merchandising, store atmosphere, and credit card usage on impulsive buying behavior. The research was conducted at KKV Bali. The data collection method used was a questionnaire. The research population consisted of KKV customers in Bali Province, with an unknown (infinite) population size, and the sample included 120 respondents. The data analysis techniques employed included Descriptive Statistical Analysis, Classical Assumption Tests, Multiple Linear Regression Analysis, F-tests, t- tests, and the Coefficient of Determination test. The research findings indicate that visual merchandising has a positive and significant effect on impulsive buying, store atmosphere has a positive and significant effect on impulsive buying, and credit card usage also has a positive and significant effect on impulsive buying. Recommendations for KKV Bali include organizing the placement of store equipment, selecting music that aligns with the store’s ambiance, consistently providing modern payment machines, expanding the scope of research, and conducting further studies in the future.